Womanhood, Love and Sacrifice: A Semiotic Analysis of the Novel “A Thousand Splendid Suns” (Journal of Asian Development Studies, 2025)
Womanhood is depicted in literature in such a way that mirrors and emphasizes the norms of a particular society, primarily through the intricate use of mythologies of love and sacrifice. The present study analyses the semiotic relationship between womanhood and oppression in Khalid Husseini's novel "A Thousand Splendid Suns" by focusing on the myths of love and sacrifice. This study also explores how Husseini constructs and deconstructs the myths of love and sacrifice to reveal the imposition of patriarchal society on an oppressed woman. Drawing on the concepts of Ronald Barthes theory of semiotics, the study's findings revealed how neutral signs carry the hidden ideologies of a society. The researcher explored the various signs and symbols that represent resilience, endurance, sacrifice, and loyalty associated with womanhood. The textual analysis provides insight into significant motifs, such as motherhood, the institution of marriage, and the sacrifice of women, which showcase their ideological roles. The findings further indicate that love and sacrifice are portrayed as noble virtues; however, they advocate for patriarchal oppression. The author's deconstruction of these myths perpetuates the idea that the way socially constructed gender is represented in literature can be challenged by empowering women.